Lipoxygenase Products in the Urine Correlate with Renal Function and Body Temperature but not with Acute Transplant Rejection. Issue 2 (29th December 2012) - Reinhold, Stephan W.; Scherl, Thomas; Stölcker, Benjamin; Bergler, Tobias; Hoffmann, Ute; Weingart, Christian; Banas, Miriam C.; Kollins, Dmitrij; Kammerl, Martin C.; Krüger, Bernd; Kaess, Bernhard; Krämer, Bernhard K.; et al.
Abstract: Acute transplant rejection is the leading cause of graft loss in the first months after kidney transplantation. Lipoxygenase products mediate pro‐ and anti‐inflammatory actions and thus we aimed to correlate the histological reports of renal transplant biopsies with urinary lipoxygenase products concentrations to evaluate their role as a diagnostic marker. This study included a total of 34 kidney transplant recipients: 17 with an acute transplant rejection and 17 controls. LTE4, LTB4, 12‐HETE and 15‐HETE concentrations were measured by enzyme immunoassay. Urinary lipoxygenase product concentrations were not significantly changed during an acute allograft rejection. Nevertheless, LTB4 concentrations correlated significantly with the body temperature ( P ≤ 0.05) 3 months after transplantation, and 12‐ and 15‐HETE concentrations correlated significantly with renal function ( P ≤ 0.05) 2 weeks after transplantation. In conclusion, our data show a correlation for LTB4 with the body temperature 3 months after transplantation and urinary 12‐ and 15‐HETE concentrations correlate positively with elevated serum creatinine concentrations but do not predict acute allograft rejection.